Seasonal monitoring of cocaine and benzoylecgonine in a subtropical coastal zone (Santos Bay, Brazil) - Fontes, Mayana Karoline [UNESP]; Campos, Bruno Galvao de [UNESP]; Cortez, Fernando Sanzi [UNESP]; Pusceddu, Fabio Hermes; Moreno, Beatriz Barbosa; Maranho, Luciane Alves [UNESP]; Lebre, Daniel Temponi; Guimaraes, Luciana Lopes; Seabra Pereira, Camilo Dias (Elsevier B.V., 2019)
Illicit drugs and their metabolites represent a new class of emerging contaminants. These substances are continuously discharged into wastewater which have been detected in the aquatic environment in concentrations ranging from ng.L(-)7(1) to mu g.L-1. Our study detected the occurrence of cocaine (COC) and benzoylecgonine (BE) in a subtropical coastal zone (Santos Bay, SP, Brazil) within one year. Water samples (surface and bottom) were collected from the Santos Submarine Sewage Outfall (SSOS) area. COC and BE were measured in the samples using ultra-performance liquid chromatography coupled to tandem mass spectrometry (UPLC-ESI-MS/MS). Concentrations ranged from 12.18 to 203.6 ng.L-1 (COC) and 8.20 to 38.59 ng.L-1 (BE). Higher concentrations of COC were observed during the end of spring, following the population increase at summer season. COC and its metabolite occurrence in this coastal zone represent a threat to coastal organisms.
Keywords: Cocaine; Benzoylecgonine; Marine pollution; Submarine sewage outfall; Contaminants of emerging concern